EFFECT OF LONG-TERM STORAGE ON POST-THAW CHARACTERISTICS OF FROZEN SEMEN OF HF CROSSBRED BULLS - SHRIVATAVA, NOOPUR; AWASTHl, M K; NAIR, A K; TIWARl, R P; POYAM, M R; MISHRA, G K (The Indian Journal of Animal Reproduction, 2023)
Frozen semen sample of three HF crossbred bulls stored for 4, 8, 12, 16, 20 and 24 months were usedto study the effect of long-term storage on post-thaw characteristics of frozen semen. Three frozen semen straws of same batch from individual bull were thawed at 37°C for 30 seconds; pooled and post-thaw motility, viability, acrosomal integrity and proportion of spermatozoa with intact functional membrane were recorded for different storage period. Post-thaw semen characteristics were compared among different storage time in individual bull. Post-thaw motility, viability, percentage of spermatozoa with intact acrosome and percentage of spermatozoa with intact functional membrane in frozen-thawed semen of all three bulls consistently and significantly decreased from 4 months onward at 8, 12, 16, 20 and 24 months (P< 0.01) during long-term storage of semen. One bull recorded less than 50 per cent post-thaw motility at 8 months of storage period onward up to 24 months in contrast to other two bulls with post-thaw motility ~ 50 per cent up to 16 months of storage. From the present study, it may be concluded that post-thaw characteristics of frozen semen stored for long period of time varied not only among different storage time but also among the bulls. Hence, assessment of post-thaw semen quality should be made prior to dispatch of long-term stored frozen semen to be used for insemination under field conditions.
Keywords: Crossbred bulls; Frozen semen; Long term storage; Post-thaw semen characteristics